The effect of the dominant muscle strength and self confidence on the results climb of the rock climbing’s athlete - Hardiyono, Bayu; Nurkadri, Nurkadri; Pratama, Budiman Agung; Laksana, Anak Agung Ngurah Putra (Universitas Nusantara PGRI Kediri, 2019)
This study aimed to determine how much influence between the four independent variables, namely leg muscle strength, abdominal muscles strength, back muscle strength, self confidence, and the climbing variable bound. The method used in this study is the path analysis method, which is an analysis technique which is used to study the causal relationship between the independent variable and the dependent variable. The sample in this study were 30 rock climbing athletes. Data analysis techniques used in this research are (1) path analysis (2) simple correlation (3) coefficient of determination. From the results of this study indicated that: (1) of the 10 problems that were formulated, all of them showed results there was a direct influence between the research variables. (2) the direct effect of leg muscle strength on the strength of the back muscles shows the highest results between the formulations of other problems.